2015
DOI: 10.1055/s-0034-1383222
|View full text |Cite
|
Sign up to set email alerts
|

Das KnorpelRegister DGOU zur Erfassung von Behandlungsergebnissen nach Knorpeloperationen: Erfahrungen nach 6 Monaten und erste epidemiologische Daten

Abstract: The German Cartilage Registry (KnorpelRegister DGOU) has been introduced in October 2013 and aims on the evaluation of patients who underwent cartilage repair for symptomatic cartilage defects. It represents a nation-wide cohort study which has been introduced by the working group "Tissue Regeneration" of the Germany Society of Orthopaedic Surgery and Traumatology and is technically based upon a web-based remote data entry (RDE) system. The present article describes first experiences with the registry includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…According to the Deutsche Gesellschaft fur Orthopaedie und Unfallchirurgie (DGOU) registry between October 2013 and June 2014, 60% of treated defects were degenerative. In a multi-centre study from 400 patients, approximately 35% had chondral lesions resulting from degenerative conditions [4,5]. Current strategies for the treatment of cartilage lesions have involved the use of surgical intervention (e.g., microfracture) or cell-based therapies [6].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Deutsche Gesellschaft fur Orthopaedie und Unfallchirurgie (DGOU) registry between October 2013 and June 2014, 60% of treated defects were degenerative. In a multi-centre study from 400 patients, approximately 35% had chondral lesions resulting from degenerative conditions [4,5]. Current strategies for the treatment of cartilage lesions have involved the use of surgical intervention (e.g., microfracture) or cell-based therapies [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that there is an increased risk of OA within the knee joint due to previous joint injury (e.g., anterior cruciate ligament (ACL) injury), excessive repetitive loading, joint dysplasia and meniscectomy. According to the German Cartilage Registry (Deutsche Gesellschaft für Orthopäedie und Unfallchirurgie (DGOU)) between October 2013–June 2014, 60% of treated cartilage defects were degenerative, whilst a recent multi-centre study showed that of 400 patients, approximately 40% had chondral injuries resulting from degenerative conditions [5,6]. In classifying the forms of OA that can be treated, recent studies have described the term “early OA” [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Autologous articular chondrocytes are an established cell-based tissue engineering strategy for treatment of large “focal traumatic” or “focal early OA” chondral or osteochondral defects of the knee joint [6,11,12]. Mesenchymal stem cells (MSCs) can be isolated from a variety of sources including bone marrow, adipose (liposuction or intrapatellar fat pad) or synovium with minimal donor site morbidity [13,14,15,16] and have been shown to have chondrogenic potential, initially in vitro with the creation of pellets or micromasses and the addition of the stimulatory growth factor, transforming growth factor-beta (TGF-β) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Among these are university medical centers and private hospitals, doctors’ surgeries, and outpatient surgical centers. As of January 31, 2016, a total of 2124 patients have been registered (see Figure 3 ) and the first clinical results have been published [ 40 - 42 ].…”
Section: Resultsmentioning
confidence: 99%